2009
DOI: 10.1002/chin.200951196
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Stereoselective Synthesis of L‐Deoxyaltronojirimycin (VII) from L‐Serine

Abstract: Carbohydrates U 0500 Stereoselective Synthesis of L-Deoxyaltronojirimycin (VII) from L-Serine -[involving ring-closing metathesis and stereoselective epoxidation as key steps]. -(RENGASAMY, R.; CURTIS-LONG, M. J.; RYU, H. W.; OH, K. Y.; PARK*, K. H.; Bull. Korean Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Based upon our previous studies, which readily produced 5 stereodefined azasugars, the C4 stereocenter was confirmed to be S for good inhibition [Rengasamy et al, 2009]. Most importantly, compound 1 was shown to be a The hydrolytic activity of α-rhamnosidase as a function of compound 1 concentration (0, ù; 3.1 μM, ø; 6.2 μM, Ă; 12.5 μM, ÿ, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon our previous studies, which readily produced 5 stereodefined azasugars, the C4 stereocenter was confirmed to be S for good inhibition [Rengasamy et al, 2009]. Most importantly, compound 1 was shown to be a The hydrolytic activity of α-rhamnosidase as a function of compound 1 concentration (0, ù; 3.1 μM, ø; 6.2 μM, Ă; 12.5 μM, ÿ, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The starting compound 6, (3R,4S)-3-Hydroxy-4-N-allyl-NBoc-amino-1-pentene, has been achieved as a single diastereomer without racemization via vinyl Grignard addition to N-Boc-N-allyl aminoaldehyde from enantio pure L-alanine [Rengasamy et al, 2008]. The other starting compound 9 was started from L-serine and proceeded via a highly stereoselective neucleophilic addition to an aminoaldehyde equivalent and ring closing metathesis using Grubbs II catalyst [Rengasamy et al, 2009]. The preparation of tetrahydropyridene 7 was achieved in 78% yield via ring closing metathesis using Grubbs II catalyst (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%